2019
DOI: 10.3928/00220124-20190814-06
|View full text |Cite
|
Sign up to set email alerts
|

Improving Adherence to a Pediatric Advanced Life Support Supraventricular Tachycardia Algorithm in Community Emergency Departments Following in Situ Simulation

Abstract: Background: Recognition and management of pediatric dysrhythmias is challenging for community emergency department (CED) providers, given their infrequent exposure to these cases. Method: A prospective, interventional study measured adherence of CEDs to pediatric supraventricular tachycardia (SVT) algorithm pre- and postimplementation of an in situ simulation-based collaborative program. CED teams' adherence was scored using a composite adherence score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…18,19 A series of recent studies successfully demonstrated the effect of in situ simulation on the skills and confidence of health-care providers in general emergency departments in treating various simulated pediatric critical conditions, such as diabetic ketoacidosis, airway management, and supraventricular tachycardia. [11][12][13][14][15] In this study, simulation was used as a tool to assess and improve the process of care provided by interprofessional teams and identifies gaps and opportunities for improvements in the system of care in the general emergency department setting. Subsequently, simulation was used as an improvement tool with which these gaps were addressed with general emergency department leadership through the development of customized performance reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 A series of recent studies successfully demonstrated the effect of in situ simulation on the skills and confidence of health-care providers in general emergency departments in treating various simulated pediatric critical conditions, such as diabetic ketoacidosis, airway management, and supraventricular tachycardia. [11][12][13][14][15] In this study, simulation was used as a tool to assess and improve the process of care provided by interprofessional teams and identifies gaps and opportunities for improvements in the system of care in the general emergency department setting. Subsequently, simulation was used as an improvement tool with which these gaps were addressed with general emergency department leadership through the development of customized performance reports.…”
Section: Discussionmentioning
confidence: 99%
“…10 In parallel, we previously reported a collaboration program between our pediatric academic medical center and a group of general emergency departments statewide. [11][12][13][14][15] This collaboration, through in situ simulation, education, and quality improvement, aimed to optimize pediatric emergency readiness and quality of care provided in general emergency departments. Participating general emergency departments demonstrated significant improvement in the process of care provided to children in acute care scenarios, including advanced airway management in a simulated setting.…”
Section: Introductionmentioning
confidence: 99%
“…Despite calls for demonstration of the value NPD practice brings to healthcare organizations (Harper & Maloney, 2022), evidence of NPD contributions to positive outcomes in children's hospitals is scarce. Although evidence is found of the value of staff education in the literature, in most cases, these data arise from quality improvement projects, both with NPD participation (Benning & Webb, 2019; Hammontree & Kinderknecht, 2022) and without NPD participation (Gavriloff, 2012; Gest, 2021; Kisting et al, 2019; Longo et al, 2008), along with academic research (Cantrell et al, 2005; Cantrell & Brown, 2006; Lutfi et al, 2019; Mariana et al, 2019; Mustafa et al, 2021). A single systematic review was found.…”
Section: Review Of Literaturementioning
confidence: 99%
“…[44][45][46][47][48][49][50][51] This work identified common gaps in care that have subsequently served as the foundation for a series of projects that have resulted in improvements in structure and process measures. 10,50,[52][53][54] Most recently, the team has examined the translation of these improvements to changes in patient outcomes. Over the past 8 years, the ImPACTS has received more than 2.5 million in funding and engaged 40 tertiary care simulation teams working with more than 250 community partners.…”
Section: Next Stepsmentioning
confidence: 99%
“…The groups work initially focused on using mixed methods to describe, measure, and compare pediatric acute care using in situ simulations for conditions, including sepsis, cardiac arrest, Diabetic Ketoacidosis, and seizures 44–51 . This work identified common gaps in care that have subsequently served as the foundation for a series of projects that have resulted in improvements in structure and process measures 10,50,52–54 . Most recently, the team has examined the translation of these improvements to changes in patient outcomes.…”
Section: Six Domains With Associated Strategiesmentioning
confidence: 99%